MEMBONGKAR RELASI TERSEMBUNYI: POLA HUBUNGAN PELAKU DAN KORBAN KEKERASAN SEKSUAL DALAM PERSPEKTIF KRIMINOLOGI - Zul Khaidir Kadir (CV. Denasya Smart Publisher, 2025)
The pattern of relationships between perpetrators and victims in sexual violence covers a wide spectrum, ranging from close relationships, unclose but known relationships, to anonymous relationships. Unfortunately, there is a lack of attention to certain relationship patterns, which has implications for weak prevention strategies and adaptive legal responses. The purpose of this study focuses on the pattern of relationships between perpetrators and victims that have so far been less explored in depth in academic literature. This study uses a qualitative research method with a conceptual approach. Data collection methods are collected using literature studies and then analyzed using qualitative methods and presented descriptively. The results of the study indicate that close relationships can involve betrayal of trust and emotional control that worsen psychological trauma, unclose but known relationships create ambiguity in proving the perpetrator's intentions, and anonymous relationships show opportunistic nature. Therefore, a victim-based approach is needed to place the needs and experiences of victims at the center of every legal process.